Cotton Cellulose-Derived Hydrogel and Electrospun Fiber as Alternative Material for Wound Dressing Application - Jirawitchalert, Supidcha; Mitaim, Samon; Chen, Ching-Yi; Patikarnmonthon, Nisa (International Journal of Biomaterials, 2022)
Cotton has been recognized as a useful biomaterial over decades, and it has been widely applied in the textile industry. However, a large amount of cotton waste is generated during the manufacturing processes, but it has been considered as a low-value product. With high content of cellulose remaining in cotton waste, our study focuses on transforming cotton cellulose into a valuable product. Cellulose was extracted from cotton waste and modified into two main materials for wound dressing application: hydrogel-based water absorbent materials and electrospun composite nanofibers. In order to enhance the water absorption, carboxymethyl cellulose (CMC), the modified cellulose with functional group prone to interact with water molecules, has been developed in this study. The hydrogel-based CMC was created by using the chemical cross-linking reaction of epichlorohydrin (ECH). The hydrogel demonstrated the swelling and reswelling ability by 1718 ± 137% and 97.95 ± 9.76%, respectively. Meanwhile, cellulose/PEG in trifluoroacetic acid (TFA) was successfully fabricated as nonwoven composite by a conventional electrospinning technique. The fabrics provided highly appropriated properties as wound dressing, including the following: water absorption was up to 1300 times and water vapor permeability controlled in the range of 2163–2285 g·m−2·day−1. This showed the preliminary information for recovering cotton waste into valuable products.